2006
DOI: 10.1029/2005gb002642
|View full text |Cite
|
Sign up to set email alerts
|

Methyl iodide production in the ocean: Implications for climate change

Abstract: [1] Methyl iodide concentrations of up to 45 pmol L À1 , which flux into the marine boundary layer, have been found in low latitude waters of the Atlantic and Indian oceans. These high concentrations correlate well with the abundance of Prochlorococcus, and we have confirmed the release of methyl iodide by this species in laboratory culture experiments. Extrapolating, we estimate the global ocean flux of iodine to the marine boundary layer from this single source to be 5.3 Â 10 11 g I yr À1 , which is a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 60 publications
7
105
3
Order By: Relevance
“…Among the reasons for this is that the analytical chemistry at the extremely low concentrations necessary to study ambient 129 I (10 -7 to 10 -11 M) have not been readily available and the analytical procedures were (and still are) arduous (Denham et al, 2009 129 I concentration was 232 pCi L -1 immediately downstream of the seepage basins (source terms) and decreased with distance from the seepage basin. 127 I concentration decreased similarly to that of 129 I. Near the seepage basins, the majority (55 -86%) of iodine existed as iodide for both 129 I and 127 I.…”
Section: Summary and Relevance Of Microbial Processes Influencing 129mentioning
confidence: 62%
See 4 more Smart Citations
“…Among the reasons for this is that the analytical chemistry at the extremely low concentrations necessary to study ambient 129 I (10 -7 to 10 -11 M) have not been readily available and the analytical procedures were (and still are) arduous (Denham et al, 2009 129 I concentration was 232 pCi L -1 immediately downstream of the seepage basins (source terms) and decreased with distance from the seepage basin. 127 I concentration decreased similarly to that of 129 I. Near the seepage basins, the majority (55 -86%) of iodine existed as iodide for both 129 I and 127 I.…”
Section: Summary and Relevance Of Microbial Processes Influencing 129mentioning
confidence: 62%
“…Schmitz and Aumann (1995) analyzed soils collected from a reprocessing plant in Germany and reported that 39 to 49% of the 129 I was associated with the water soluble fraction, whereas only 4 to 15% was associated with the organic and 7 to 13% was associated with the residual fraction. However, a different distribution of stable iodine, 127 I, was observed where only <4% occurred in the water soluble fraction. This difference between the two isotopes may be attributed to the different sources of the two isotopes and underscores an important point that the fate of iodine in the environment is controlled by more than just geochemical behavior.…”
Section: Sorption To Sediment Minerals and Organic Matter 331 Iodinmentioning
confidence: 98%
See 3 more Smart Citations